Prevalence of High Epworth Sleepiness Scale Scores in a Rural Population - P Pahwa; CP Karunanayake; L Hagel; JA Gjevre; D Rennie; J Lawson; JA Dosman (Canadian Respiratory Journal)
BACKGROUND: Increased daytime sleepiness is an important symptom of obstructive sleep apnea (OSA). OSA is frequently underdiagnosed, and the Epworth Sleepiness Scale (ESS) can be a useful tool in alerting physicians to a potential problem involving OSA.